Continental scale dietary patterns in a New World raptor using web-sourced photographs - Panter, Connor T. (2024)
Dietary studies are essential to better understand raptor ecology and resource requirements through time and space, informing species habitat use, interspecific interactions and demographic rates. Methods used to collect data on raptor diets can constrain how dietary analyses can be interpreted. Traditional approaches to study raptor diets, such as analysis of pellets or prey remains, often provide dietary data at the local population level and tend to be restricted to pairs during the breeding season. The increasing use of citizen science data has the potential to provide dietary inferences at larger spatial, demographic and temporal scales. Using web-sourced photography, we explore continental-scale demographic and latitudinal dietary patterns between adult and non-adult Crested Caracaras (Caracara plancus), throughout the species’ range across the Americas. We analysed 1,555 photographs of caracaras feeding and found no age effects on the probabilities of different food groups being included in photographs. The probability of reptiles being included in photographs of caracaras from the northern population was significantly higher than those from the southern population, with the opposite pattern for birds. There were significant latitudinal effects with the probabilities of fishes and invertebrates in the diet of northern caracaras increasing towards the equator. Contrastingly, the probability of mammals in the diet increased away from the equator for both populations. Assuming the focal species is well-sampled, websourced photography can improve our understanding of raptor diets at large-scales and complements more traditional approaches. This approach is more accessible to raptor researchers without access to the field or expertise in physical prey identification techniques.